2006
DOI: 10.1007/s00428-006-0299-x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of metaloproteinases-2 and -9 is different according to the patterns of growth and invasion in squamous cell carcinoma of the penis

Abstract: Squamous cell carcinoma (SCC) of the penis is characterized by different patterns of growth and local invasion. The matrix metalloproteinases (MMPs) is a family of proteolytic enzymes that are involved in the degradation of extracellular matrix to allow the migration of tumor cells. The present study examined whether the expression of MMP-2 and -9 is correlated with the patterns of tumor growth and invasion in penile SCC. The expression of MMP-2 and -9 was examined immunohistochemically in samples of 115 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(41 reference statements)
0
4
0
2
Order By: Relevance
“…As activation of TGF-β/Smad2/3 pathway has already been demonstrated to be involved in the malignant progression and dissemination of various cancer types, it would be reasonable to propose that the effects of CEACAM19 might partly result from its function in regulating the Smad2/3 activation, thus promoting the metastasis of penile cancer 34. Soares et al showed that penile cancers with over-expression of two metastasis-related molecules MMP2 and MMP9 were deeply invasive 35. Similarly, we observed that the secretion of MMP2 and MMP9 was markedly down-regulated in Penl1 cells with CEACAM19 knockdown or treated with TGF-β/Smad2/3 inhibitor SB431542, suggesting CEACAM19 might regulate the metastatic phenotype of penile cancer via modulating Smad2/3 and its downstream MMP2/9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…As activation of TGF-β/Smad2/3 pathway has already been demonstrated to be involved in the malignant progression and dissemination of various cancer types, it would be reasonable to propose that the effects of CEACAM19 might partly result from its function in regulating the Smad2/3 activation, thus promoting the metastasis of penile cancer 34. Soares et al showed that penile cancers with over-expression of two metastasis-related molecules MMP2 and MMP9 were deeply invasive 35. Similarly, we observed that the secretion of MMP2 and MMP9 was markedly down-regulated in Penl1 cells with CEACAM19 knockdown or treated with TGF-β/Smad2/3 inhibitor SB431542, suggesting CEACAM19 might regulate the metastatic phenotype of penile cancer via modulating Smad2/3 and its downstream MMP2/9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases (RR = 57.9; 95% CI = 7.4 -453.9), urethral infiltration (RR = 3.5; 95% CI = 1.3 -9.2) and MMP-9 immunoreactivity (RR = 3.2; 95% CI = 1.2 -8.3) were considered independent risk factors for disease recurrence. Soares et al [112] examined whether the expression of MMP-2 and MMP-9 is different according to the patterns of tumor growth and invasion in 115 patients with SCC of the penis. The findings of this series allowed it to be concluded that less differentiated tumors, which are more invasive and with a pattern of invasion in small group of cells, are associated with the overexpression of MMPs.…”
Section: Tumor Markers and Prognosismentioning
confidence: 99%
“…Papers analyzing even the most common molecules involved with carcinogenesis, tumor progression and metastases are scarce in the literature. Almost nothing is known about penile SCC genetics and molecular markers, especially when compared with knowledge about SCC from other sites, such as cervical and head/neck tumors [112] . The author's department, from 1953 to 2000, has recorded 799 patients with penile carcinoma.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Foi analisado o percentual de células neoplásicas coradas, considerando apenas expressão citoplasmática nas células tumorais. Os casos foram graduados conforme o seguinte critério: 0 -negativa: < 5% de células; 1 -positividade fraca: 5% a 20% das células; 2 -positividade moderada: 21% a 50% das células; 3 -positividade forte: > 50% (32) .…”
Section: Análise Imuno-histoquímicaunclassified
“…Assim, a invasão de um tumor epitelial é uma etapa essencial para a progressão do câncer, incluindo os tumores de esôfago (6) . Nesse sentido, a degradação dos componentes da matriz extracelular confere ao tumor de esôfago a possibilidade de invasão local para tecidos adjacentes, além de permitir o acesso aos vasos sanguíneos e linfáti-cos, proporcionando a disseminação a distância (5,32,36) . A degradação dos componentes da matriz extracelular é mediada por uma família de enzimas proteolíticas, denominadas metaloproteinases de matriz (MMPs).…”
Section: Introductionunclassified